Flow of granular materials through orifices - Haider, Syed Jawad; Mackey, Robert D.; Chai Muktabhant; Moh, Za-Chieh (Bangkok : Asian Institute of Technology, 1968)
Using dry sand, the factors affecting the flow of granular materials through circular orifices were studied under gravity conditions. Tests were conducted on four uniformly-graded fractions of Bangkok river sand. Showering techniques were employed to pack the granular mass at different porosities. It was observed that the height of fill did not affect the rate of flow which varied approximately as the cube of the orifice diameter. The flow rate was appreciably affected by the effective particle size and the porosity of the granular mass. The critical orifice diameter, at which flow ceased completely, was obtained for each sand grading and the effect of porosity on this diameter was determined. Also, the flow pattern was observed in a perspex cylinder and it was concluded that sand flows out via a conical channel formed directly above the orifice.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering in the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1968
Keywords: Bulk solids flow; Sand